Limitations of current chemotherapy and future of nanoformulation-based AmB delivery for visceral leishmaniasis—An updated review - Kumar, Prakash; Kumar, Pawan; Singh, Nidhi; Khajuria, Salil; Patel, Rahul; Rajana, Vinod Kumar; Mandal, Debabrata; Velayutham, Ravichandiran (Frontiers in Bioengineering and Biotechnology, 2022)
Visceral leishmaniasis (VL) is the most lethal of all leishmaniases if left untreated. Despite the fact that it is the second most common infectious disease after malaria, leishmaniasis, a parasitic disease, has been categorized as a neglected tropical disease. According to the latest WHO study, >20 Leishmania species spread 0.7–1.0 million new cases of leishmaniasis each year. VL, which is caused by the Leishmania donovani genus, affects between 50,000 and 90,000 people worldwide each year. There is a lack of new drug development, trolling numbers in drug resistance cases, drug toxicity with even potential treatment candidate, Amphotericin B (AmB). Also, no availability of a significant vaccine, intend the researchers to find a way to develop a nanoparticle-based formulation for the first choice of the drug-like AmB. Since AmB is an old medicinal molecule, it's been used to treat VL in a variety of FDA-approved formulations. The cornerstone of AmB's limitations is nephron and liver toxicity. Many nanoparticle-based formulations have been developed to address these challenges, ranging from liposomal nanoparticles to more sophisticated quantum dot-based drug delivery systems. Notably, nanoparticle-based delivery has shown increased efficacy due to the targeted delivery of the payload and the synergistic impact of NP and payload on the target. The development of AmB formulation delivery over traditional chemotherapy is examined in this review, also the current clinical status of AmB in VL, most probable mechanisms of action in Leishmania donovani parasite, drug toxicity in the host system. Clinical trial data on an AmB-based formulation for leishmaniasis and the prospective possibilities of NP-based administration as a possible novel therapeutic candidate is also updated.